Defining ‘Future Generations’: Epistemic Considerations on Conceptualizing a Future-Oriented Domain in Policy And Law-Making - Knudsen Mikkel Stein; Ahlqvist Toni; Taylor Amos (Tamkang University, 2025)
The rights of future generations generates increasing interest among both academics and policymakers. This article identifies two key gaps in the emerging literature. First, based on a systematic literature review, futures researchers’ recent contributions to the subfield are surprisingly subdued compared to those of other research fields. The article calls for renewed engagement from futurists. Second, the literature and policy documents are surprisingly vague on epistemic considerations conceptualising the boundaries of future generations. The articles provide novel insights to this theme through a survey of 65 Finnish and international futures scholars and foresight experts. Considering alternative conceptualizations of future generations may help enable for considering future generations’ interest in policy and law-making.